(untitled) - Appleyard, Dennis R. (New York, 2006)
Appleyard, Field, and Cobb’s International Economics 5e offers a consistent level of analysis and treatment of the two main subdivisions of international economics—international trade theory and policy and international monetary theory and policy. Comprehensive and clear, the text helps students move beyond recognition toward and understanding of current and future international events. A new co-author, Steven L. Cobb from the University of North Texas, joins the book this edition and brings expertise especially in the fields of economic education and transition economies, particularly those in Eastern Europe.
Keywords: International economic relations,International trade,International finance,Tài chính quốc tế,Thương mại quốc tế,Quan hệ kinh tế quốc tế